Two distinct etiologies of gastric cardia adenocarcinoma: interactions among pH, Helicobacter pylori, and bile acids - Mukaisho, Ken-ichi; Nakayama, Takahisa; Hagiwara, Tadashi; Hattori, Takanori; Sugihara, Hiroyuki (Frontiers in Microbiology, 2015)
Gastric cancer can be classified as cardia and noncardia subtypes according to the anatomic site. Although the gastric cancer incidence has decreased steadily in several countries over the past 50 years, the incidence of cardia cancers and esophageal adenocarcinoma (EAC) continue to increase. The etiological factors involved in the development of both cardia cancers and EACs are associated with high animal fat intake, which causes severe obesity. Central obesity plays roles in cardiac-type mucosa lengthening and partial hiatus hernia development. There are two distinct etiologies of cardia cancer subtypes: one associated with gastroesophageal reflux (GER), which predominantly occurs in patients without Helicobacter pylori (H. pylori) infection and resembles EAC, and the other associated with H. pylori atrophic gastritis, which resembles noncardia cancer. The former can be developed in the environment of high volume duodenal content reflux, including bile acids and a higher acid production in H. pylori–negative patients. N-nitroso compounds, which are generated from the refluxate that includes a large volume of bile acids and are stabilized in the stomach (which has high levels of gastric acid), play a pivotal role in this carcinogenesis. The latter can be associated with the changing colonization of H. pylori from the distal to the proximal stomach with atrophic gastritis because a high concentration of soluble bile acids in an environment of low acid production is likely to act as a bactericide or chemorepellent for H. pylori in the distal stomach with H. pylori infection. The manuscript introduces new insights in causative factors of adenocarcinoma of the cardia about the role of bile acids in gastro-esophageal refluxate based upon robust evidences supporting interactions among pH, H. pylori, and bile acids.